Sodium and Potassium Content of the Most Commonly Available Street Foods in Maputo, Mozambique - Jessen, N (2022)
Street foods can contribute largely for dietary sodium intake of populations in developing countries. We aimed to assess the variability in sodium and potassium composition of the most commonly available homemade street foods in Maputo city, capital of Mozambique. In a cross-sectional evaluation, researchers canvassed areas with 500-m diameter centered around 20 randomly selected public transport stops, identified all street food vending sites and, in randomly selected sites, purchased 56 samples of the most frequently available homemade foods. Samples were analyzed for sodium and potassium concentrations, using flame photometry. The 56 samples represented main dishes (45 samples of 12 types of food item), sandwiches (8 samples of 5 types of food item) and fried snacks (3 samples of 2 types of food item). Median contents (range), in mg/serving, were 921 (198 to 2525) of sodium and 385 (24 to 1140) of potassium. Median (range) of sodium to potassium molar ratio was 4.1 (1.3 to 41.5). One serving of main dishes was estimated to contribute from 32.1% to 99.9% of the recommended maximum daily sodium intake. The present study shows a large variability and potential for improvement in sodium and potassium contents of homemade foods frequently available in the streets of Maputo city.